Treatment of murine partial thickness scald injuries with multipotent adult progenitor cells decreases inflammation and promotes angiogenesis leading to improved burn injury repair. Issue 3 (2nd March 2021) - Ahangar, Parinaz; Mills, Stuart J.; Smith, Louise E.; Strudwick, Xanthe L.; Ting, Anthony E.; Vaes, Bart; Cowin, Allison J.
Abstract: Stem cells have been shown to have potential as a new therapy for burns and promote wound healing through decreasing inflammation and increasing angiogenesis. Multipotent adult progenitor cells (MAPC® cells) are a subpopulation of bone marrow‐derived stem cells with outstanding self‐renewal and differentiation capacity. MAPC cells also secrete a wide range of cytokines which can affect cellular activities. This article aimed to examine the effects of MAPC cells treatment on burn injury repair using a mouse model of partial thickness burn injury. The immunomodulatory effect of MAPC cells was investigated in vitro using a simultaneous T‐cell proliferation assay. Partial thickness burns were created on the dorsal surface of mice and MAPC cells were administered via intradermal injection to the wound margins 24 h post‐burn injury. The burn tissues were analysed macroscopically to determine wound area and histologically assessed to determine wound width and rate of re‐epithelialisation. Immunohistochemistry and ELISA were employed to assess cell proliferation, inflammation and angiogenesis and collagen deposition in the burn area. MAPC cells inhibit the proliferation of stimulated T cells in culture. Burns intradermally injected with MAPC cells showed a significant reduction in the macroscopic wound area, histologic wound width and had an increased rate of re‐epithelialisation. Immunohistochemistry and ELISA analysis of burn tissues showed dampened inflammation evidenced by a reduction in neutrophilic infiltration and modulation of inflammatory cytokines. Angiogenesis within the burn area was also improved in MAPC cell treated mice. However, no significant effect of MAPC cell treatment was observed on extracellular matrix production. Treatment of burns with MAPC cells improved burn injury repair with reduced time to healing, decreased inflammation and increased angiogenesis. These findings demonstrate the promising effects of MAPC cells on burn injury repair and suggest MAPC cells as a candidate source for clinical cell therapies.